Education on the Importance of Good Nutrition in Infants and Toddlers in the Johar Baru II Puskesmas Community - Agustina Ida Pratiwi; Lorensia Panselina Widowati; Dyah Woro Kartiko kusumo Wardani (Jurma : Jurnal Program Mahasiswa Kreatif, 2022)
Nutrition is a chemical component found in food and required by the body that can determine the quality of children's development and growth. The World Health Organization (WHO) global data from 2017 states that 22.2% of young children worldwide suffer from nutritional problems. And more than half (55%) are in Asian countries and Indonesia is in the top 5 places. The nutritional problems experienced in Indonesia are experienced by many young children due to many factors, for example, the problem of poverty and the problem of parents' lack of knowledge about nutritional supplements for young children. From the analysis of the data obtained in the Johar Baru 2 community data assessment on November 9-12, 2020, out of 20 infants, 2 infants had irregular eating habits, 1 infant did not eat vegetables. And out of the 20 toddlers, 2 toddlers still have poor nutritional status (yellow), 8 toddlers have a habit of snacking, most kinds of snacks are sweets. The method used in this activity is to provide advice on the importance of good nutrition for infants and young children. The activities are conducted online and are aimed at families with infants and young children. After completing the consultation, the participants' knowledge of good nutrition for small children increased by 21% per question.